Cardiopulmonary assessment through stress testing - Ang, Kok Chiang (2008)
This dissertation presents the results from a collaborative project between Nanyang Technological University and Singapore General Hospital (Department of Respiratory and Critical Care Medicine). Three studies were conducted with interpretative strategies and clinical indications of performing indices for the purpose of monitoring disease progression and response to rehabilitation treatment.